Peran Digital Marketing Memediasi Pengaruh Orientasi Pasar terhadap Kinerja Pemasaran UMKM Busana Adat Bali - Putu Intan Astarani; I Wayan Santika; I Gde Ketut Warmika; Satria Pramudana (Journal Of Business, Finance, and Economics (JBFE), 2025)
MSMEs in Balinese traditional clothing are starting to develop rapidly, which can be seen from the growth of the Balinese traditional clothing business. This research aims to test and analyse the role of digital marketing mediates the impact of market orientation on marketing performance. This research was conducted in Tabanan Regency, Bali Province. Tabanan Regency, Bali Province. The population in this research were traders who sold Balinese traditional clothing products in Tabanan Regency, Bali Province. The sampling method used in this research is non-probability sampling with purposive sampling technique. sampling with purposive sampling technique. The number of samples determined in this research were 100 respondents. Data were collected through questionnaires and analysed using path analysis, classical assumption test, and sobel test. The results of this research indicate that digital marketing is a partial mediating variable of the influence between market orientation on the marketing performance of MSMEs of Balinese Traditional Clothing. This can be used for other MSME management to make policies in paying attention to or increasing market orientation so that it will increase digital marketing performance. increasing market orientation so that it will increase digital marketing, with increasing digital marketing it will improve marketing performance.